2022
DOI: 10.3390/microorganisms10091792
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids: Major Regulator of the Gut Microbiome

Abstract: Bile acids are synthesized from cholesterol and play an important role in regulating intestinal microflora. The different degrees of hydrophobicity and acidity of individual bile acids may affect their antimicrobial properties. We examined the antimicrobial effects of different bile acids on various microorganisms in vitro and confirmed whether these remain consistent in vivo. Using human bile acids, including ursodeoxycholic acid, cholic acid, chenodeoxycholic acid, deoxycholic acid, and lithocholic acid, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The relationship between PPIs and infectious diseases of the biliary system has been discussed in several clinical studies ( Chuang et al, 2019 ; Min et al, 2019 ). The biliary system typically maintains a sterile environment with bile acids ( D'Aldebert et al, 2009 ); however, a recent study proposes that there is a clear transfer of intestinal microorganisms to the biliary tract in patients with biliary tract diseases ( An et al, 2022 ). Additionally, animal models of SIBO revealed that intestinal flora and metabolites can affect bile acid metabolism and cause biliary disease ( Almeida et al, 2013 ); overall, this establishes a correlation between biliary system disease and the intestinal microbiota.…”
Section: Ppi-induced Digestive System Complicationsmentioning
confidence: 99%
“…The relationship between PPIs and infectious diseases of the biliary system has been discussed in several clinical studies ( Chuang et al, 2019 ; Min et al, 2019 ). The biliary system typically maintains a sterile environment with bile acids ( D'Aldebert et al, 2009 ); however, a recent study proposes that there is a clear transfer of intestinal microorganisms to the biliary tract in patients with biliary tract diseases ( An et al, 2022 ). Additionally, animal models of SIBO revealed that intestinal flora and metabolites can affect bile acid metabolism and cause biliary disease ( Almeida et al, 2013 ); overall, this establishes a correlation between biliary system disease and the intestinal microbiota.…”
Section: Ppi-induced Digestive System Complicationsmentioning
confidence: 99%
“…Although different defense mechanisms have been highlighted in intestinal microorganisms (i.e., active efflux system, DNA repair, and cell envelope remodeling), it is known that BAs can directly and indirectly influence gut microbiota composition through bacteriostatic and bactericidal effects and regulation of host immunity ( 67 , 111 113 ).…”
Section: Bas and Obesity: Current Knowledgementioning
confidence: 99%
“…In the small intestine, BAs emulsify dietary fats, fat-soluble vitamins, and other lipids. Under the influence of the anaerobic bacterial flora in the intestine, a number of primary BA transformations occur, including deconjugation and dehydroxylation, which lead to the formation of secondary BAs, i.e., DCA and LCA [ 60 , 61 , 62 , 63 , 64 ]. As a result of further changes, under the influence of both hepatic and intestinal mechanisms, substances of minor importance are formed, i.e., tertiary BAs: HDCA and UDCA.…”
Section: Bile Acidsmentioning
confidence: 99%